Synthesis, antimicrobial and antifungal activity of 3-(2-bromophenyl)-5-(alkylthio)-4-phenyl-4H-1,2,4-triazoles - Safonov, A. A.; Panasenko, O. I.; Сафонов, Андрій Андрійович; Панасенко, Олександр Іванович (Запорізький державний медичний університет, 2022)
The aim of the work was to synthesize and investigate antimicrobial and antifungal activity among 3-(2-bromophenyl)-5-(alkylthio)-4- phenyl-4H-1,2,4-triazoles. Materials and methods. It was used 5-(2-bromophenyl)-4-phenyl-4H-1,2,4-triazole-3-thiol as a starting substance, which was synthesized by previously described techniques. 3-(2-Bromophenyl)-5-(alkylthio)-4-phenyl-4H-1,2,4-triazoles were obtained by alkylation of the starting thiol with halohenalkanes (according to the first method) and the addition of hydrochloric acid in an alcoholic medium, then subsequent heating in microwave synthesis system (by the second method). To study the antimicrobial and antifungal activity of the newly synthesized 3-(2-bromophenyl)-5-(alkylthio)-4-phenyl-4H-1,2,4-triazoles, the method of serial dilutions was used according to guidelines. Results. 3-(2-Bromophenyl)-5-(alkylthio)-4-phenyl-4H-1,2,4-triazoles were obtained by two methods: a) an equivalent amount of halohenalkane was added to 5-(2-bromophenyl)-4-phenyl-4H-1,2,4-triazole-3-thiol (I) (solvent – KOH pre-dissolved in 2-propanol). Boiled to pH = 7; b) 5-(2-bromophenyl)-4-phenyl-4H-1,2,4-triazole-3-thiol (I) (solvent – methyl or 1-propyl alcohol and 10 drops of HCl) was heated in Milestone Flexi Wave microwave synthesis system. Reaction conditions: The mixture was heated for 45 minutes at a temperature of 150 °C, a pressure 14.4 bar, ΔMW ≈ 200 W. The completeness of the reaction was determined using a gas chromatograph Agilent 7890B with a mass spectrometric detector 5977B. Antimicrobial and antifungal activity of 3-(2-bromophenyl)-5-(alkylthio)-4-phenyl-4H-1,2,4- triazoles (6 new compounds) was investigated. The most active compound with antifungal and antimicrobial effect was IIi. Substances IIa–IIe had moderate antimicrobial effect. Мета роботи – синтез і дослідження протимікробної та протигрибкової активності нових 3-(2-бромфеніл)-5-(алкілтіо)-4-феніл-4H- 1,2,4-тріазолів. Матеріали та методи. Як вихідну речовину застосували 5-(2-бромфеніл)-4-феніл-4H-1,2,4-тріазол-3-тіол, який синтезували за попередньо наведеними методиками. 3-(2-Бромфеніл)-5-(алкілтіо)-4-феніл-4H-1,2,4-тріазоли одержали шляхом алкілування вихідного тіолу галогеналканами (за першим методом) і додаванням хлороводневої кислоти в спиртовому середовищі з нагріванням надалі в системі мікрохвильового синтезу (за другим методом). Для вивчення протимікробної та протигрибкової активностей нових синтезованих 3-(2-бромофеніл)-5-(алкілтіо)-4-феніл-4Н-1,2,4-тріазолів використали метод серійних розведень згідно з рекомендаціями. Результати. 3-(2-Бромофеніл)-5-(алкілтіо)-4-феніл-4Н-1,2,4-тріазоли отримували двома методами: а) еквівалентну кількість галогеналкану додавали до 5-(2-бромофеніл)-4-феніл-4Н-1,2,4-тріазол-3-тіолу (I) (розчинник – 2-пропанол, у якому попередньо розчинений КОН); кип’ятили до рН = 7; б) 5-(2-бромофеніл)-4-феніл-4Н-1,2,4-тріазол-3-тіол (I) (розчинник – метанол або 1-пропанол і 10 крапель HCl) нагрівали в системі мікрохвильового синтезу Milestone Flexi Wave; умови реакції: час – 45 хвилин, температура – 150 °C, тиск – 14,4 бар, ΔMW ≈ 200 Вт. Повноту реакції визначали за допомогою газового хроматографа Agilent 7890B з мас-спектрометричним детектором 5977B. Дослідили протимікробну та протигрибкову активності 3-(2-бромофеніл)-5-(алкілтіо)-4-феніл-4Н-1,2,4-тріазолів. Найактивніша сполука з протигрибковим і протимікробним ефектами – IIi. Речовини IIa–IIe мають помірну протимікробну дію.
Синтез, протимікробна та протигрибкова активність 3-(2-бромфеніл)-5-(алкілтіо)-4-феніл-4H-1,2,4-тріазолів
Safonov A. A. - ORCID ID: 0000-0003-2861-1826; Panasenko O. I. - ORCID ID: 0000-0002-6102-3455.
Keywords: organic synthesis; antimicrobial activity; antifungal activity; 1,2,4-triazole; heterocyclic compounds; органічний синтез; протимікробна активність; протигрибкова активність; 1,2,4-тріазол; гетероциклічні сполуки